Sustainable management of brownfield greenspace: a study of Worldwide Landfills Park Air Hitam, Puchong, Malaysia - Raja Yahya, Raja Nur Atikah; Mohamad Taram, Emran @ Zahrin; Othman, Abd Aziz (Universiti Putra Malaysia Press, 2019)
Decades ago, landfills were designed and operated on the outskirts of the city. However, due to the sprawl of urbanization, many residential areas have been developed around the landfill areas. Therefore, the environmental and hazardous issues such as landfill gas, leachate and foul odour have risen up. As the greenspaces have recently decreased, Malaysia government in 2010 suggested that the ex-landfill areas which are part of the brownfields should be turned into valuable urban greenspaces. This study thus reviews the management practices of closed landfill to become a sustainable greenspace. A case study was carried out at the Worldwide Landfills Park Air Hitam Puchong, Selangor Malaysia. It is the first ex-landfill in Klang Valley Malaysia developed as a park. Two research methods were adopted for this study, namely key informant approach and secondary data analysis. The result indicated that the safe closure and post-closure management including leachate management and landfill gas management using the gas collection system have successfully rehabilitated the site into a park. A reduction of CO2e using landfill gas collector and natural absorber i.e. vegetation is also discussed in this review.